Modeling relation among implementing AI-based drones and sustainable construction project success - Waqar, Ahsan; Othman, Idris; Hamah Sor, Nadhim; Alshehri, Abdullah Mohammed; Almujibah, Hamad R.; Alotaibi, Badr Saad; Abuhussain, Mohammed Awad; Bageis, Abdulrahman S.; Althoey, Fadi; Hayat, Saleh; Benjeddou, Omrane; Alsulamy, Saleh Hamed; et al. (Frontiers in Built Environment, 2023)
Project failure is a persistent challenge in the construction industry, rendering it one of the most demanding sectors. Many obstacles, including safety concerns, quality management issues, environmental preservation challenges, economic sustainability, privacy constraints, and legal regulations, weigh heavily on construction projects. However, a beacon of hope emerges in AIpowered drones capable of surmounting these challenges and paving the path to resounding project success. This study employed diverse methodologies, engaging subject-matter experts through interviews and conducting pilot and primary surveys. Our analytical arsenal featured Exploratory Factor Analysis (EFA) for the pilot survey and Structural Equation Modelling (SEM) for the primary survey. Our research revolves around a singular mission: elevating building project success byThis is a provisional file, not the final typeset article dismantling the barriers that have impeded the widespread adoption of AI-driven drones in construction. The study's verdict is clear: privacy and legal constraints, coupled with economic and sustainability challenges, alongside human resource management dilemmas, constitute the formidable triumvirate obstructing the ubiquitous embrace of drones in construction. Yet, the impact of breaching these barriers reverberates far beyond overcoming these hurdles. It cascades into public health and safety, environmental conservation, quality management, and economic sustainability, culminating in an amalgam of enhanced Building Project Success. The implications of our findings are profound for the construction industry. They beckon the sector to confront and surmount the legal and regulatory barriers to adopting AI-based drones. A clarion call to invest in human resources to empower technology integration resounds. And, perhaps most importantly, it beckons the industry to embrace the profound economic and sustainability advantages of embracing these cutting-edge technologies. Furthermore, our study underscores that adopting AI-powered drones in construction isn't merely about project success; it catalyzes fostering public health, safeguarding the environment, ensuring top-tier quality management, and fortifying economic sustainability. These interwoven facets illuminate the broader canvas of drone technology's transformative role in construction.